Pendugaan umur simpan tepung pisang berdasarkan parameter kandungan air kritis - Yusuf, Mega Ayu; Jamaludin, Jamaludin; Camara, Gode Vridus Titi; Limbongan, Amelia Agustina (AGRICOLA, 2024)
Banana (Musa paradisiaca) is a fruit that contains many minerals, vitamins and carbohydrates. There are various types of bananas that are popular among people. Starting from commercial bananas which have a high market value to bananas in processed form. This research was conducted to estimate the shelf life of banana flour using the Accelerated Shelf-Life Testing method which refers to the Arrhenius Model where the critical parameter is water content. The banana used is the kepok banana type at the No.2 ripeness level with the characteristics of the banana skin still being green but showing a tinge of yellow at the tip of the fruit accompanied by black dots around the surface of the banana skin. The packaging uses polyethylene film (thickness 0.10). Each package contains a 100 gram sample. Samples were stored at different conditions, namely 30oC, 35oC, 40oC and 55oC in an atmosphere with 80% relative humidity (RH) for eight weeks of storage. Once every week, samples are evaluated for critical water content. The research results showed that the sample packaging in polyethylene film was able to last up to 2.3159 months.